Partial anomalous pulmonary venous connection and an incidental aberrant right subclavian artery: A rare case report - Ashish Khadka, MD; Aakash Neupane, MBBS; Pramodman Singh Yadav, MBBS; Leeza Shah, MD; Abinash Dev, MBBS; Sabin Ghale, MBBS, MBBS; Amisha Karki, MBBS (Radiology Case Reports)
Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital heart defect where some pulmonary veins drain into the right atrium instead of the left. We report a case of a 20-year-old female with worsening dyspnea and intermittent chest pain. Imaging revealed cardiomegaly and pulmonary hypertension on chest X-ray. Contrast-enhanced CT showed normal right pulmonary vein drainage but anomalous drainage of the left pulmonary veins into the left brachiocephalic vein. An incidental finding of an aberrant right subclavian artery (ARSA) was also noted. The patient underwent successful surgical correction of PAPVC, with no postoperative complications, though long-term follow-up was unavailable. PAPVC is often asymptomatic but can lead to right-sided heart failure and pulmonary hypertension if untreated. ARSA, a rare anomaly, was not clinically significant in this case. This report emphasizes the role of advanced imaging in diagnosing rare anomalies like PAPVC and ARSA, where early detection and intervention are crucial for preventing complications like right ventricular dysfunction and arrhythmias.